Implementing E-governance in bangladesh using cloud computing technology - Aveek, Mahfuz Aziz; Rahman, Md. Sakibur (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2011.